Competence and Professional Care of External Auditor on Information Technology Audit - Muhamad Sandi Akbar; Ida Suraida (TRIKONOMIKA, 2017)
The purpose of this study is to determine the influence of competence and professional care of external auditor on information technology audit in the public accounting firm in Bandung. The method used in this research was survey method with descriptive and verification approach, as well as by using primary data. According to the research, competence partially had no effect on information technology audit, while professional care partially affected the information technology audit. On the other words, competence and due professional care simultaneously influenced information technology audit significantly by 54.7%, while 45.3% was influenced by other variables not studied e.g independence, software usage auditing, performance auditing.